2012
DOI: 10.3390/molecules17033202
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemoprevention by Carotenoids

Abstract: Carotenoids are natural fat-soluble pigments that provide bright coloration to plants and animals. Dietary intake of carotenoids is inversely associated with the risk of a variety of cancers in different tissues. Preclinical studies have shown that some carotenoids have potent antitumor effects both in vitro and in vivo, suggesting potential preventive and/or therapeutic roles for the compounds. Since chemoprevention is one of the most important strategies in the control of cancer development, molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
293
0
10

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 501 publications
(307 citation statements)
references
References 234 publications
(304 reference statements)
4
293
0
10
Order By: Relevance
“…As antioxidants, carotenoids may reduce oxidative damage due to environmental exposures and by normal metabolic processes in the body. [9][10][11] Reactive oxygen species damage genetic material and cellular machinery, increasing the likelihood of abnormal cell growth and impaired communication. Carotenoids also have antiproliferative properties, inhibiting cell growth and angiogenesis and increasing cell differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As antioxidants, carotenoids may reduce oxidative damage due to environmental exposures and by normal metabolic processes in the body. [9][10][11] Reactive oxygen species damage genetic material and cellular machinery, increasing the likelihood of abnormal cell growth and impaired communication. Carotenoids also have antiproliferative properties, inhibiting cell growth and angiogenesis and increasing cell differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids absorb free radicals, protecting cells from oxidative damage, and may also inhibit cell growth and angiogenesis, increasing apoptosis and the immune response. 1,[9][10][11][12][13][14] To our knowledge, no previous prospective studies have assessed adolescent dietary carotenoid intake in relation to BBD risk in young women. We examined this association in the Growing Up Today Study (GUTS), a prospective cohort initiated in childhood.…”
mentioning
confidence: 99%
“…Thus, inhibiting this vicious cycle has the potential to delay, prevent the progression of and/or treat these diseases. However, the adverse effects of the current anti-inflammatory drugs [82,83] and the failure of exogenous antioxidant administration [29] should encourage scientists to develop new therapeutic alternatives.…”
Section: Chemopreventionmentioning
confidence: 99%
“…The biological basis for the concept of oral premalignancy has been established by carcinogenesis studies [7,[28][29][30].…”
Section: Leukoplakiamentioning
confidence: 99%
“…Preclinical studies have shown that some carotenoids have potent antitumor effects both in vitro and in vivo models. Since chemoprevention is one of the most important strategies in the control of cancer development, molecular mechanismbased cancer chemoprevention using carotenoids seems to be an attractive approach (Tanaka et al, 2012).…”
Section: Anticancer Mechanismmentioning
confidence: 99%